Desert Harmony: Exploring the Cultural, Social, and Economic Value of a Multi-Arts Festival in the Remote Barkly Region. Issue 2 (2nd July 2020) - Bartleet, Brydie-Leigh; Sunderland, Naomi; Woodland, Sarah; O'Sullivan, Sandy
Abstract : This article examines the role that the arts sector plays in supporting and sustaining communities in one of Australia's remotest regions, the Barkly (Northern Territory). Drawing on findings from a three-year Australian Research Council Linkage project, 'Creative Barkly', the article outlines how artistic and creative activities in very remote regions, such as the Barkly, constitute significant cultural, social, and economic value. To illustrate this, the article explores one such example, the annual Desert Harmony Festival, run by Barkly Regional Arts. This example demonstrates how an event such as this can provide a site of diverse intercultural expression that promotes both social and economic linkages and networks and generates cultural vitality in the region.